2013
DOI: 10.1189/jlb.0912475
|View full text |Cite
|
Sign up to set email alerts
|

Gfi-1 is the transcriptional repressor ofSOCS1in acute myeloid leukemia cells

Abstract: Silencing of SOCS1, a TSG, has been detected in various malignancies, including AML. However, the underlying mechanism of SOCS1 inactivation remains elusive. In this study, we explored the role of histone methylation in SOCS1 expression in AML cells. By ChIP assay, we demonstrated that G9a and SUV39H1, two enzymes catalyzing H3K9 methylation, were physically associated with the SOCS1 promoter, and treatment with chaetocin, a histone methyltransferase inhibitor, suppressed H3K9 methylation on the SOCS1 promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…A previous study demonstrated that short-term treatment (8 and 16 h) of chaetocin did not alter global H3K9 tri-methylation. 27 We also found similar results (data not shown). However, long-term treatment of chaetocin indeed reduced the methylation of H3K9 and H3K27 ( Figure 3 ) indicating this drug indeed changes histone methylation status in vivo .…”
Section: Discussionsupporting
confidence: 80%
“…A previous study demonstrated that short-term treatment (8 and 16 h) of chaetocin did not alter global H3K9 tri-methylation. 27 We also found similar results (data not shown). However, long-term treatment of chaetocin indeed reduced the methylation of H3K9 and H3K27 ( Figure 3 ) indicating this drug indeed changes histone methylation status in vivo .…”
Section: Discussionsupporting
confidence: 80%
“…Gfi1 is able to bind to a large number of promoters and enhancers (76) and plays a central role in gene silencing through the recruitment of repressive modulators including histone methyltransferases, HDACs, and histone demethylases (7779). Gfi1 has been shown to directly interact with G9a (78, 80) and Gfi1-deficient cells display a significant decrease in H3K9 methylation (78).…”
Section: Interactions and Potential Roles Of G9amentioning
confidence: 99%
“…Chaetocin was the first reported specific S-Adenosyl-methionine (SAM)-competitive inhibitor of the histone methyltransferase SUV39H1 [27], gaining much attention since deregulated epigenetic modifiers such as histone methyltransferases (HMTs) and DNA methyltransferases (DNMTs) have recently emerged as promising new drug targets [28]. SUV39H1 inhibition with chaetocin or RNAi-mediated SUV39H1 knockdown led to reduced tri-methylation of lysine 9 in histone 3 (H3K9me3), re-expression of silenced tumor suppressor genes and apoptosis induction in vitro and reduced tumor growth in vivo [26, 29]. Recently chaetocin has also been shown to not only reduce H3K9me3 levels, but also tri-methylation of lysine 27 in histone 3 (H3K27me3) in AML cell lines [30].…”
Section: Introductionmentioning
confidence: 99%